Prior assessment of CO2 leak rate through cracks sealed by nanoparticle gels - Olatunji Olayiwola; Vu Nguyen; Ning Liu; Boyun Guo (Journal of Petroleum Exploration and Production Technology, 2023)
Abstract The leakage of hydrocarbon fluids through cracks in the annular cement and CO2 storage is a major concern to the Petroleum Industry. A significant risk is posed when repairing leakage in a micro annuli channel with smaller apertures. A low-viscosity sealant that can generate a long-lasting resilient seal is desired. The solution to sealing these channels might lie in a novel application using nano-silica Gel. In this study, laboratory tests were carried out to examine the capabilities of nano-silica gels to seal the cracks. Analyzing its rheological property, the gel strengths of nano-silica gels were found to increase with an increase in nano-silica concentration. Additionally, it was discovered that as the concentration of nano-silica increases, the sealing and leakage pressures, defined as the pressures before and after water breakthrough, respectively, increase as well. With a typical 15% concentration of nano silica in gel, a sealing pressure gradient of 80.2 psi/in and a leakage pressure gradient of 30 psi/in at a leaking rate of 1 cc/min were noted. To validate the validity of the experimental results, a mathematical model was developed to predict the leakage rate of sealed fractures. The model suggests that the young’s modulus of sealant is a key property of nano-sealants and further investigations are needed to validate the mathematical model for quantitative use. This study suggests a novel strategy for enhancing cement zonal isolation and reducing cement failure in oil and gas sector.